2022
DOI: 10.1088/1742-6596/2204/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of PAHs (polycyclic aromatic hydrocarbons) and other main components in black crusts collected from the Monumental Cemetery of Milan (Italy)

Abstract: The present work focuses on the chemical characterization of some chemical components present in black crusts collected from the Monumental Cemetery of Milan located in the homonymous city (Northern Italy). Samples of black crusts, recovered over two sampling campaigns, were analysed by using X-ray Diffraction and Fourier Transform-Infrared spectroscopy. Moreover, Ionic chromatography analyses were performed on water extracts of the black crust samples, while High Performance Liquid Chromatography measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…They are composed of multiple fused aromatic rings and have a characteristic planar structure. PAHs are persistent environmental pollutants and can be found in black crusts and stone [67,68]; these molecules can be extracted from the matrix and then analyzed by high-performance liquid chromatography (HPLC) [69]. The amount of PAHs found in black crust can be up to 20 ppm [70].…”
Section: Particulate Matter and Organic Fractionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are composed of multiple fused aromatic rings and have a characteristic planar structure. PAHs are persistent environmental pollutants and can be found in black crusts and stone [67,68]; these molecules can be extracted from the matrix and then analyzed by high-performance liquid chromatography (HPLC) [69]. The amount of PAHs found in black crust can be up to 20 ppm [70].…”
Section: Particulate Matter and Organic Fractionmentioning
confidence: 99%
“…Combustion-type sources are characterized by a wide range of PAHs, while petroleum and organic sources produce lighter PAH molecules. All studies have suggested that the combustion source is the predominant one [69][70][71][72][73].…”
Section: Particulate Matter and Organic Fractionmentioning
confidence: 99%
“…In particular, stone materials are strongly damaged by air pollution in urban areas characterized by high anthropogenic emissions [24]. In the limestone's case, for example, black crusts are a common alteration of this material, due to the interaction of sulphur dioxide, PM10, and acidic rain [25,26]. It is well known that NOx concurr in the acidification of rain, thus these Major degradation results in cultural heritagescompounds are important in the degradation of limestone, [27].…”
Section: Introductionmentioning
confidence: 99%
“…Different air pollutants, comprising carbon dioxide (CO2), nitrogen dioxide (NO2), hydrogen sulfide (H2S), sulfur dioxide (SO2), particulate matter, and some persistent organic pollutants, have negative effects on cultural heritage [7][8][9][10][11][12][13][14][15], and at high concentrations can pose risks to human health [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%